2014
DOI: 10.1111/dme.12461
|View full text |Cite
|
Sign up to set email alerts
|

High normal albuminuria is independently associated with aortic stiffness in patients with Type 2 diabetes

Abstract: High normal albuminuria is associated with aortic stiffness in patients with Type 2 diabetes, which may in part explain their increased cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…In terms of arterial stiffness, previous studies reported positive associations of low-grade albuminuria with baPWV and carotid-femoral PWV in normoalbuminuric patients with T2DM [11,12]. In the present study, the strength of the association between ACR and baPWV was attenuated after adjustment for SBP and DBP both in multivariate logistic and regression models, suggesting that the effect was largely mediated by hemodynamic mechanisms.…”
Section: Comparison With Previous Reportssupporting
confidence: 44%
See 1 more Smart Citation
“…In terms of arterial stiffness, previous studies reported positive associations of low-grade albuminuria with baPWV and carotid-femoral PWV in normoalbuminuric patients with T2DM [11,12]. In the present study, the strength of the association between ACR and baPWV was attenuated after adjustment for SBP and DBP both in multivariate logistic and regression models, suggesting that the effect was largely mediated by hemodynamic mechanisms.…”
Section: Comparison With Previous Reportssupporting
confidence: 44%
“…Population-based studies showed that mortality rate increases with increasing urine albumin-to-creatinine ratio (ACR), and this relation starts before ACR reaches the levels considered as microalbuminuria [5]. Several studies found a significant association between high normal albuminuria and increased carotid intima-media thickness (IMT) [6e10] and arterial stiffness [11,12], both of which are surrogate markers of changes in vascular morphology and function. These findings highlight the possibility that lowgrade albuminuria may play a role in the pathogenesis of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Even though A1 is defined as normal ACR, this study classified category A1 into four subgroups of ≥20 and <30 mg/g, ≥10 and <20 mg/g, ≥5 and <10 mg/g, and <5 mg/g. This is because many reports demonstrated that high ACR within the normal range is associated with other diseases [22-24]. …”
Section: Discussionmentioning
confidence: 99%
“…The Singapore Study of Macro-angiopathy and Micro-vascular Reactivity in Type 2 Diabetes (SMART2D) is a cross-sectional study conducted between August 2011 and February 2014 including a total of 2057 adults aged 21e90 years with T2DM [21]. The participants were recruited consecutively from a secondary hospital and a neighboring primary-care public outpatient clinic in equal proportion in Singapore.…”
Section: Study Population and Designmentioning
confidence: 99%